HUBUNGAN KETERLIBATAN AYAH DALAM PENGASUHAN TERHADAP PERKEMBANGAN SOSIAL ANAK USIA DINI (DI PAUD TERPADU NEGERI BINA TARUNA SOBANG KABUPATEN PANDEGLANG PROVINSI BANTEN) - Amalia Putri; Hunainah; Yahdinil Firda Nadhirah (Cakrawala Pedagogik, 2026)
This research aims to determine the relationship between father involvement in parenting on the social development of early childhood at PAUD Terpadu Negeri Bina Taruna Sobang. The background of this study is based on the phenomenon of low paternal participation in childrearing activities, which affects children’s social abilities such as interaction, empathy, and cooperation. This study employed a quantitative method, with data collected through a questionnaire distributed to 25 fathers as respondents. Data were analyzed using IBM SPSS Statistics, employing t-test and F-test to examine the effect between the variables of father involvement (X) and early childhood social development (Y). The results showed that the level of father involvement in parenting was categorized as high, and children’s social development was categorized as good. Statistical analysis indicated that the t-count (4.311) > t-table (2.069) and the Sig. value (0.000) < 0.05, which means there is a positive and significant influence between father involvement in parenting and the social development of early childhood. The higher the level of father involvement, the better the child’s social abilities, such as empathy, cooperation, responsibility, and social discipline. In conclusion, father involvement plays an essential role in supporting the social development of early childhood. Therefore, active paternal participation in parenting should be encouraged through collaboration between families and early childhood education institutions.